Bioefficacy of Commonly Used Insecticides Against Rice Brown Planthopper, Nilaparvata lugens (STÃ…L) - SATENDRA K MANGRAUTHIA, V. RATNAKAR, V. JHANSI LAKSHMI C. SRINIVAS, R. JAGADEESHWAR and (The Journal of Research, PJTSAU, 2020)
Studies on the bio-efficacy of commonly used insecticides against brown planthopper (BPH), Nilaparvata lugens (Stål)population were carried out at ICAR-Indian Institute of Rice Research, Hyderabad during 2017. To assess efficacy of insecticidesagainst BPH population, the insecticides were diluted to specified doses with water and sprayed on 60 day old potted TN1 riceplants with the help of fine atomizer and 7-9 day old nymphs of BPH were released and confined to treated plants. Observationson BPH mortality were recorded at 2, 24, 48 and 72 hours after release of nymphs. The results revealed that after two hours oftreatment, dichlorvos recorded highest per cent mortality i.e. 62.5. Dinotefuran and chlorpyriphos recorded 100 per cent mortalityafter 24 hours of insecticidal treatment followed by dichlorvos (88.7%), thiamethoxam (85.0%), fipronil (85.0%), ethiprole (79.2%),monocrotophos (70.0%), acephate (65.0%), imidacloprid (53.7%), combination product ethiprole + imidacloprid (48.7%) andpymetrozine (38.7%). Buprofezin recorded least per cent mortality i.e. 32.5. With the progression of time (48 and 72 hours afterapplication of insecticides), the mortality of BPH nymphs increased in all the treatments. Dinotefuran, dichlorvos, chlorpyriphos,thiamethoxam, monocrotophos, ethiprole and fipronil were found to be highly effective against BPH while acephate, ethiprole +imidacloprid, imidacloprid and pymetrozine were moderately effective. Buprofezin failed to control BPH.